2017
DOI: 10.1016/j.celrep.2016.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Axl Mediates ZIKA Virus Entry in Human Glial Cells and Modulates Innate Immune Responses

Abstract: ZIKA virus (ZIKV) is an emerging pathogen responsible for neurological disorders and congenital microcephaly. However, the molecular basis for ZIKV neurotropism remains poorly understood. Here, we show that Axl is expressed in human microglia and astrocytes in the developing brain and that it mediates ZIKV infection of glial cells. Axl-mediated ZIKV entry requires the Axl ligand Gas6, which bridges ZIKV particles to glial cells. Following binding, ZIKV is internalized through clathrin-mediated endocytosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
432
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(459 citation statements)
references
References 44 publications
22
432
0
5
Order By: Relevance
“…Evidence from clinical and animal studies indicates that ZIKV is unique among flaviviruses in that it can persist in testes (9,10) and fetal brain (11)(12)(13). Consistent with this idea, studies from our laboratory and others have revealed multiple mechanisms used by ZIKV to evade the host interferon system (14)(15)(16), an indispensable antiviral response that controls ZIKV infection and pathogenesis (17,18). How the virus counteracts other cellular antiviral pathways is largely unknown.…”
mentioning
confidence: 71%
“…Evidence from clinical and animal studies indicates that ZIKV is unique among flaviviruses in that it can persist in testes (9,10) and fetal brain (11)(12)(13). Consistent with this idea, studies from our laboratory and others have revealed multiple mechanisms used by ZIKV to evade the host interferon system (14)(15)(16), an indispensable antiviral response that controls ZIKV infection and pathogenesis (17,18). How the virus counteracts other cellular antiviral pathways is largely unknown.…”
mentioning
confidence: 71%
“…ZIKV can bind to target cells using adhesion factors such as DC-SIGN and phosphatidylserine binding receptors (Hamel et al, 2017) from which Axl appeared as the main receptor for the entry in human skin fibroblasts (Hamel et al, 2015), microglia (Meertens et al, 2017), astrocytes (Retallack et al, 2016;Meertens et al, 2017) and blood-brain barrier endothelial cells . Surprisingly, Axl does not seem to be necessary for the entry of ZIKV in NPC and cerebral organoids (Wells et al, 2016;Meertens et al, 2017), despite the high expression of this receptor in NSC and NPC (Cugola et al, 2016;Liu et al, 2016;Nowakowski et al, 2016;Onorati et al, 2016;Meertens et al, 2017). Replication and assembly of progeny virions of ZIKV take place onto modified membranes derived from the endoplasmic reticulum.…”
Section: Mechanisms Of Zikv Entry In Human Cells and The Antiviral Rementioning
confidence: 99%
“…The activation of p53 was not restricted to NPC expressing high levels of viral antigens (Ghouzzi et al, 2016), suggesting that this might be an early event or an indirect effect of ZIKV infection in neighboring cells. Other cell types, such as microglia, astrocytes, and endothelial cells, can also be infected Lum et al, 2017;Meertens et al, 2017), but it is unknown how the interplay among different cell types contribute to the outcome of microcephaly.…”
Section: Are There Any Differences In the Neurovirulence Of Differentmentioning
confidence: 99%
“…It has recently been reported that ZIKV entry into cells requires the AXL ligand, Gas6, which bridges the viral particles to glial cells, where the virus is then internalized [29,30]. During the viral entry of the cell, the ZIKV/Gas6 complex activates AXL kinase activity, which dampens the interferon response to the virus and facilitates infection [29,31,32].…”
Section: Aravive-s6mentioning
confidence: 99%
“…During the viral entry of the cell, the ZIKV/Gas6 complex activates AXL kinase activity, which dampens the interferon response to the virus and facilitates infection [29,31,32]. It has recently been reported that Aravive Biologic's engineered decoy AXL receptor, Aravive-S6, can block ZIKV infection by intercepting Gas6 to prevent AXL signaling [29].…”
Section: Aravive-s6mentioning
confidence: 99%